OPPORTUNITIES AND LIMITATIONS OF USING THE METHOD OF REAL OPTIONS IN EVALUATION OF INNOVATION PROJECTS - Elena Makarova; Maria Novoselova (Вестник Северо-Кавказского федерального университета)
The purpose of this study is to investigate the possibilities and limitations of using the real option method when evaluating innovative projects. To achieve this goal, an analysis of the theoretical, analytical, empirical and methodological support for the implementation of innovative projects was made, based on the results of which the main characteristics of the real options method were determined. The main limitations of using the real option method are the necessity to ensure the receipt of reliable initial data, the risk of overstating the cost of a loss-making innovative project, the revision ofplans and the risks of not achieving the company's goals, lack of a support in the company's corporate culture and lack of qualified specialists, and decision support tools for structuring real options in innovative projects. To build the management of innovative projects from the standpoint of the methodology of real options, it is necessary to implement the algorithm for determining real options presented in the article.